Programming Microsoft Visual Basic .NET (Core Reference) - Williams, Mickey (Microsoft Press, 2011)
Accelerate your productivity with Visual Basic® .NET—and quickly create powerful Win32® applications and high-performance, scalable applications for the Web—with this indispensable tutorial and reference. Building on the success of the author’s popular programming book for Visual Basic 6.0, this new book teaches you the best practices for porting and reusing existing Visual Basic code in the .NET Framework as well as for exploiting the language’s advanced new object-oriented capabilities. It covers the common language runtime (CLR), multithreaded programs, Windows® Forms applications, GDI+ graphic programming, Windows services, ADO.NET classes for database programs, ASP.NET Web Forms, and Web Services. It includes advanced optimization techniques and tips for leveraging the power of the Microsoft® Visual Studio® .NET environment.